Preparation of water-soluble hyperbranched polyester nanoparticles with sulfonic acid functional groups and their micelles behavior, anticoagulant effect and cytotoxicity - Han, Qiaorong (Langmuir : the ACS journal of surfaces and colloids, 2013)
Biocompatibility of nanoparticles has been attracting great interest in the development of nanoscience and nanotechnology. Herein, the aliphatic water-soluble hyperbranched polyester nanoparticles with sulfonic acid functional groups (HBPE-SO3 NPs) were synthesized and characterized. They are amphiphilic polymeric nanoparticles with hydrophobic hyperbranched polyester (HBPE) core and hydrophilic sulfonic acid terminal groups. Based on our observations, we believe there are two forms of HBPE-SO3 NPs in water under different conditions: unimolecular micelles and large multimolecular micelles. The biocompatibility and anticoagulant effect of the HBPE-SO3 NPs were investigated using coagulation tests, hemolysis assay, morphological changes of red blood cells (RBCs), complement and platelet activation detection, and cytotoxicity (MTT). The results confirmed that the sulfonic acid terminal groups can substantially enhance the anticoagulant property of HBPE, and the HBPE-SO3 NPs have the potential to be used in nanomedicine due to their good bioproperties